2020
DOI: 10.5334/aogh.2433
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Stunting in Children under the Age of 5 in Rural Guatemalan Highlands

Abstract: Background: Previously, a study conducted by UNICEF found that malnutrition affects approximately 80% of the indigenous children in Guatemala. Objective: Identify prevalence and risk factors for stunted growth in communities surrounding Lake Atitlán, Guatemala. Methods: Height-forage measurements of children under the age of five, N = 84, determined stunting prevalence and presumed burden of malnutrition in this region of the Guatemalan highlands. Mothers of a subset of this sample, N = 29, were interviewed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
1
14
0
3
Order By: Relevance
“…In this case, unfiltered sources of drinking water and bad personal hygiene make it easier for infectious diseases to occur. This is in line with other studies which state that there is a relationship between environmental hygiene and sanitation with the occurrence of stunting as these condition can predict the occurrence of stunting in children 33 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this case, unfiltered sources of drinking water and bad personal hygiene make it easier for infectious diseases to occur. This is in line with other studies which state that there is a relationship between environmental hygiene and sanitation with the occurrence of stunting as these condition can predict the occurrence of stunting in children 33 .…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, for not consuming sufficient amount of milk. 33 . Whereas, a reserach in Uganda on millet porridge as the main food for children reveals that they could only meet <60% of the recommended daily nutritional intake 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A smaller study in the Guatemalan highlands found that indigenous children (mean age 2.6 years) with >1 caregiver-reported illness (all-cause) per month did have increased risk of stunting, though they did not measure neurodevelopment. 35 Other potential explanations are that pathogens in this community differ and/or that background rates of diarrhea are high enough in this community 36 that our case definition (caregiver report of > 3 loose stools/24 hours) did not adequately differentiate children with and without illness, or what is considered abnormal. Additionally, the type of inflammation and inflammatory pathways in diarrheal illness may be different than respiratory diseases, or they may be pathogen-specific to organisms less prevalent in this community.…”
Section: Discussionmentioning
confidence: 95%
“…Growth hormone affects cortical bone deposition and may stimulate growth and height gain. To anticipate this, an adequate nutritional intervention must be carried out [5].…”
Section: The Relationship Between Maternal Height and The Incidence O...mentioning
confidence: 99%